Identification of novel Xanthomonas euvesicatoria type III effector proteins by a machine‐learning approach. (15th August 2015) - Teper, Doron; Burstein, David; Salomon, Dor; Gershovitz, Michael; Pupko, Tal; Sessa, Guido
Summary: The Gram‐negative bacterium X anthomonas euvesicatoria ( X cv ) is the causal agent of bacterial spot disease in pepper and tomato. X cv pathogenicity depends on a type III secretion (T3S) system that delivers effector proteins into host cells to suppress plant immunity and promote disease. The pool of known X cv effectors includes approximately 30 proteins, most identified in the 85‐10 strain by various experimental and computational techniques. To identify additional X cv 85‐10 effectors, we applied a genome‐wide machine‐learning approach, in which all open reading frames (ORFs) were scored according to their propensity to encode effectors. Scoring was based on a large set of features, including genomic organization, taxonomic dispersion, hypersensitive response and pathogenicity ( hrp )‐dependent expression, 5′ regulatory sequences, amino acid composition bias and GC content. Thirty‐six predicted effectors were tested for translocation into plant cells using the hypersensitive response (HR)‐inducing domain of AvrBs2 as a reporter. Seven proteins (XopAU, XopAV, XopAW, XopAP, XopAX, XopAK and XopAD) harboured a functional translocation signal and their translocation relied on the HrpF translocon, indicating that they are bona fide T3S effectors. Remarkably, four belong to novel effector families. Inactivation of the xop AP gene reduced the severity of disease symptoms in infected plants. A decrease in cell death and chlorophyll content was observed in pepper leaves inoculated with the xop AP mutant when compared with the wild‐type strain. However, populations of the xop AP mutant in infected leaves were similar in size to those of wild‐type bacteria, suggesting that the reduction in virulence was not caused by impaired bacterial growth.